The influence of different carrier agents and drying techniques on physical and chemical characterization of Japanese quince (Chaenomeles japonica) microencapsulation powder. (1st September 2020) - Turkiewicz, Igor Piotr; Wojdyło, Aneta; Tkacz, Karolina; Lech, Krzysztof; Michalska-Ciechanowska, Anna; Nowicka, Paulina
Highlights: Freeze-drying resulted in the highest retention of polyphenols. The major group of phenolic compounds in the powders comprised flavan-3-ols. Maltodextrin was found to be the best biopolymer for obtaining high-quality powder. The use of inulin caused a 3-fold increase in HMF content compared to maltodextrin. Japanese quince juice powders inhibited α-glucosidase and pancreatic lipase. Abstract: Fruit powders can become a new and innovative direction of using the potential of Japanese quince (JQ) fruit in an affordable form. Therefore, physical (dry matter, true and bulk density, porosity and color) and chemical parameters of JQ juice powders obtained by using different carrier agents and drying techniques were evaluated. The juice was mixed with maltodextrin, inulin and a mixture of both in different proportions and dried using freeze, spray, and vacuum (50, 70, and 90 °C) drying techniques. The identification and quantification of phenolic compounds in JQ juice powders were performed by LC–PDA–QTOF–MS and UPLC-PDA, respectively, while antioxidant capacity was measured using ABTS, FRAP and ORAC assays. In addition, enzymatic in vitro inhibition tests of α-glucosidase, pancreatic lipase, acetylcholinesterase and 15-lipoxygenase were performed. Among the drying techniques applied, freeze-drying resulted in the highest retention of polyphenols, while among the carrier agents maltodextrin was found to be the best biopolymer for obtaining high-quality fruit powder and also ensured powders with the lowest content of undesirable hydroxymethylfurfural.